Doing good, feeling good: causal evidence from volunteers. Issue 3 (3rd July 2022) - Deri Armstrong, Catherine; Devlin, Rose Anne; Seifi, Forough
Abstract : Volunteers are reputedly healthier and happier than their non-volunteering counterparts. But is this a causal link or are healthier, happy individuals simply more likely to volunteer? Some papers have attempted to identify the causal relationship using an instrumental variable methodology, mostly relying on measures of religiosity as instruments for volunteering – however, religiosity may also affect health thus calling into question the validity of this approach. We rely on a novel instrument, a measure physical proximity to volunteer opportunities, to help identify the causal link from volunteering to health and happiness using econometric regression techniques. We find that volunteering is a robustly significant predictor of health, and positively affects life satisfaction for all but those aged under 35.